Entrepreneurship and Social Responsibility in Education as Key to Sustainable Development (Docentes 2.0 Journal, 2024)
Entrepreneurial activities may vary depending on the discipline or teaching specialty. This work focuses on those that have a greater impact on the economy. The objective was to determine the influence of university teaching topics such as entrepreneurship and social responsibility on students to achieve sustainable development in their country. The research was based on a systematic literature review under the interpretive paradigm, quantitative approach, basic type, documentary design, and cross-sectional. A population of 30 authors were considered who mentioned the three keywords entrepreneurship, social responsibility, and sustainable development; the sample was 15 authors due to the relevance of their results. The technique was a meta-analysis of the registration form instrument. The results mentioned that the countries with the greatest interest were from the European continent, followed by the Asian countries, in which the variables of entrepreneurship and social responsibility were of interest but associated with sustainable development, which was still in development. This work was validated with the studies defined in the citations of other authors, and it was concluded that strengthening entrepreneurship and social responsibility skills leads to the sustainable development of regions or countries.
Keywords: Entrepreneurship; social responsibility; sustainable development